Rancang Bangun Smart Trash Bin Automation pada Smartlab Politeknik Negeri Jakarta - Irfan Alhady, Muhamad; Yudha Raharja, Bima; Fuadi Hasani, Rifqi (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
Smartlab is a new laboratory in Department of Electrical Engineering, Jakarta State Polytechnic. The lab is designed to support the latest research in the telecommunications field, including the implementation of automation for the systems and items in the lab. The development of a Smart Trash Bin Automation is one of the ongoing projects. Using information and digital technology, it aids in the management and handling of waste collection. This research has created the Smart Trash Bin Automation system, which is connected to the internet using Arduino Uno Rev3 and ESP-32. This module is responsible for processing and sending data from the trash bins to a smartphone. The smartphone use Blynk application, which receives data when the systems sends notification to the users when the trash bin reaches its maximum capacity. Smart Trash Bin Automation is also equipped with an ultrasonic sensor that detects objects inside the trash bin. If an object is detected, the trash bin will open automatically, eliminating the need for users to touch the trash bin directly. The system has been tested successfully, with all devices functioting as intended. Keywords—Arduino, ESP-32, Smartlab, Smart Trash Bin Automation, Ultrasonic sensor.